Institutional Investors, Political Connections, and the Incidence of Regulatory Enforcement Against Corporate Fraud - Wu, Wenfeng (Journal of business ethics, 2016)
We investigate two under-explored factors in mitigating the risk of corporate fraud and regulatory enforcement against fraud, namely institutional investors and political connections. The role of institutional investors in the effective monitoring of a firm’s management is well established in the literature. We further observe that firms that have a large proportion of their shares held by institutional investors have a lower incidence of enforcement actions against corporate fraud. The importance of political connections for enterprises, whether in a developed market such as the United States or an emerging market such as China, has been established by previous studies. However, we find evidence of another positive effect of political connections: they may reduce the incidence of enforcement action against corporate fraud. We also find that political connections play a more significant role in reducing regulatory enforcement incidents against non-state-owned enterprises and firms in weaker legal environments, whereas institutional ownership plays a more important role in reducing regulatory enforcement incidents against state-owned enterprises.